PENERAPAN NILAI NILAI MULTIKULTURAL DALAM PENDIDIKAN ISLAM DI INDONESIA, YORDANIA DAN TURKI: KAJIAN KOMPARATIF LITERATUR - Ainul Rofiqo; Ariffah Nargis Tasliyah; Nurul Fajriah Wati; Mohammad Khoirul Anam; Umar Faruq; Zainul Arifin (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This study aims to analyze and compare the implementation of multicultural values within Islamic education in Indonesia, Jordan, and Turkey. The research employs a comparative literature review using content analysis of academic sources, government policies, and curriculum documents. The findings indicate that all three countries emphasize religious moderation, tolerance, justice, and dialogue as key foundations of Islamic education, yet each implements these values according to its socio-political context. Indonesia highlights multiculturalism grounded in ethnic diversity and pesantren tradition, Jordan focuses on religious moderation and counter-extremism, while Turkey balances Islamic ethics with nationalism within its secular educational framework. Specific findings reveal differences in curriculum structure, institutional models, and social orientations. The study implies that Indonesia must strengthen systematic multicultural education policies, enhance teacher training, and optimize the role of pesantren and schools as key environments for developing inclusive and moderate learners.